Faktor-Faktor yang Mempengaruhi Kebijakan Pengungkapan Corporate Social Responsibility dalam Laporan Tahunan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Roslin Roslin; Ethika Ethika (Jurnal Kajian Akuntansi dan Auditing, 2019)
This research was aimed to p rove some factors affecding disclosure policy of corporate social responsibility on company’s annual report. These factors are leverage, profitability, supervisory boards size, company size, managerial ownership, and foreign stock ownership. This research used purposive sampling to get sample was 11 manufacturing companies which has registered in Indonesia stock exchange since 2007 until 2011. The analysis design of this research was multiple linear regression analysis with SPSS program. The result of this research showed that foreign stock ownership has significant effect toward disclosure policy of corporate social responsibility. While leverage, profitability, supervisory boards size, company size, managerial ownership do not have effect toward disclosure policy of corporate social responsibility